PEMBENTUKAN KARAKTER MELALUI DONGENG PADA ANAK USIA DINI - Maghfiroh, Lailatul (Universitas Islam Darul Ulum, 2024)
Abstract In this millennium era, storytelling activities are rarely done by parents to children because storytelling culture has been considered old-fashioned. Instead, children prefer to play games or cellphones rather than reading. Character building in early childhood has an important role in shaping personality and morals in the future. One effective and fun method in this process is through storytelling. This research method is literature study research and includes descriptive qualitative research. The data source of this research is data obtained from written sources using content analysis. The results of this study show that character building through fairy tales in early childhood is an effective and fun method to instill moral and ethical values. In the process of storytelling, the use of expression, voice intonation, and props can increase children's understanding of the moral message conveyed. This research also highlights strategies and techniques for delivering fairy tales that are appropriate to the stages of child development, ranging from toddler age to early elementary school. With a consistent and creative approach, fairy tales become an effective tool in shaping children's character as a whole. Keywords: Character Building, Fairy Tales, Early Childhood